PENINGKATAN HASIL BELAJAR JARING-JARING BALOK DAN KUBUS DENGAN PENDEKATAN PEMBELAJARAN MATEMATIKA REALISTIK DI SEKOLAH DASAR - Yelvia, Yelvia (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
The purpose of this researcher is to increase of studi jaring-jaring balok and kubus result by using Realistic Matematika Teaching at class IV SD Negeri !9 Halalang Kabupaten Agam. This research is using qualitative and quantitative approach. This class measure research is consist of activity cycle by 3 time study. The research is using four step activity . That is planning, execution, supervision and reflection. The research subject is teacher and students at class IV SD Negeri 19 Halalang  Kabupaten Agam number in 14 person. The research instrument is observation sheet and question test. The research result is showed goadeis  a) RPP cycle I is 71.43 at cycle II become 89.28. b) Study activity at teacher aspect cycle is 68.75 at cycle II become 87.50 and c) The study result rate cycle I kognitive, afective, and psycomotor aspect is 69.35 at cycle II become 83.75. So the conclusion that realistic matematics teaching approach can increase study jaring-jaring balok and kubus result at elementary scool. Kata Kunci : hasil belajar, jaring-jaring balok kubus, pendekatan pembelajaran matematika realistik.